2004
DOI: 10.1038/sj.onc.1207210
|View full text |Cite
|
Sign up to set email alerts
|

IG20, in contrast to DENN-SV, (MADD splice variants) suppresses tumor cell survival, and enhances their susceptibility to apoptosis and cancer drugs

Abstract: We identified seven putative splice variants of the human IG20 gene. Four variants namely, IG20, MADD, IG20-SV2 and DENN-SV are expressed in human tissues. While DENN-SV is constitutively expressed in all tissues, expression of IG20 appears to be regulated. Interestingly, overexpression of DENN-SV enhanced cell replication and resistance to treatments with TNFa, vinblastine, etoposide and c-radiation. In contrast, IG20 expression suppressed cell replication and increased susceptibility to the above treatments.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 38 publications
0
35
0
Order By: Relevance
“…However, IG20pa rendered cells highly susceptible to apoptosis induced by different death signals including TRAIL, and suppressed cell proliferation. In contrast, we had found that DENN-SV is overexpressed in tumor tissues and cancer cell lines, and expression of exogenous DENN-SV could confer resistance to apoptosis and enhance cell proliferation (Al-Zoubi et al, 2001;Efimova et al, 2003Efimova et al, , 2004Ramaswamy et al, 2004). These observations indicated that IG20-SVs could differentially regulate cell proliferation and death.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…However, IG20pa rendered cells highly susceptible to apoptosis induced by different death signals including TRAIL, and suppressed cell proliferation. In contrast, we had found that DENN-SV is overexpressed in tumor tissues and cancer cell lines, and expression of exogenous DENN-SV could confer resistance to apoptosis and enhance cell proliferation (Al-Zoubi et al, 2001;Efimova et al, 2003Efimova et al, , 2004Ramaswamy et al, 2004). These observations indicated that IG20-SVs could differentially regulate cell proliferation and death.…”
Section: Discussionmentioning
confidence: 92%
“…The IG20 gene plays an important role in cancer cell proliferation, apoptosis and survival Lee, 1996, 1998;Schievella et al, 1997;Brinkman et al, 1999;Murakami-Mori et al, 1999;Telliez et al, 2000;AlZoubi et al, 2001;Lim and Chow, 2002;Efimova et al, 2003Efimova et al, , 2004Lim et al, 2004;Ramaswamy et al, 2004). Additionally, it plays an important role in neurotransmission (Zhang et al, 1998;Tanaka et al, 2001;Yamaguchi et al, 2002), neurodegeneration (Del Villar and Miller, 2004) and guanine nucleotide exchange (Wada et al, 1997;Brown and Howe, 1998;Iwasaki and Toyonaga, 2000;Levivier et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also the IG20 gene, which appears to have at least seven splice variants, encodes for a protein involved in the TNF-alpha signaling pathway; overexpression of its isoform DENN-SV, the only one expressed in normal brain, enhances cell replication and resistance to TNFalpha, vinblastine, etoposide and g-radiation, supporting the antiapoptotic and cell survival role of DENN-SV (Efimova et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…One example is provided by IG20, a splice variant of MADD (MAP-K activating death domain-containing protein). IG20 is a protein interacting with the tumor necrosis factor alpha (TNFa) receptor (Al-Zoubi et al, 2001) and TNF-related apoptosis-inducing ligand) (TRAIL) receptor (Efimova et al, 2003). Through its activities, IG20 sensitizes the cell to apoptotic stimuli and induces the secretion of interleukin (IL)-6, thus suppressing tumor cell growth (BS Prabhakar, personal communication).…”
Section: The Induction Of Cellular Senescence and Cell Cycle Checkpoimentioning
confidence: 99%